2016
DOI: 10.1371/journal.pone.0151257
|View full text |Cite
|
Sign up to set email alerts
|

Development of Microsatellite Markers and Analysis of Genetic Diversity and Population Structure of Colletotrichum gloeosporioides from Ethiopia

Abstract: Twenty three polymorphic microsatellite markers were developed for citrus plant pathogenic fungus, Colletotrichum gloeosporioides, and were used to analyze genetic diversity and population structure of 163 isolates from four different geographical regions of Ethiopia. These loci produced a total of 118 alleles with an average of 5.13 alleles per microsatellite marker. The polymorphic information content values ranged from 0.104 to 0.597 with an average of 0.371. The average observed heterozygosity across all l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 101 publications
1
40
0
1
Order By: Relevance
“…Comparatively, a high genetic diversity was observed on C. gloeosporioides in yam in Nigeria using 51 SSR markers (Abang et al, ) and on strawberry in the United States using 40 genetic loci with RAPD and SSR markers (Urena‐Padilla, Mackenzie, Bowen, & Legard, ). Using 50 SSR markers, including the 10 SSR markers we tested, Moges et al () found a higher level of genetic diversity between 163 Ethiopian Citrus C. gloeosporioides isolates. Because polyacrylamide gels are less sensitive to detect small size variations of SSR amplicons than capillary electrophoresis used by Moges et al (), we may have detected fewer alleles in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Comparatively, a high genetic diversity was observed on C. gloeosporioides in yam in Nigeria using 51 SSR markers (Abang et al, ) and on strawberry in the United States using 40 genetic loci with RAPD and SSR markers (Urena‐Padilla, Mackenzie, Bowen, & Legard, ). Using 50 SSR markers, including the 10 SSR markers we tested, Moges et al () found a higher level of genetic diversity between 163 Ethiopian Citrus C. gloeosporioides isolates. Because polyacrylamide gels are less sensitive to detect small size variations of SSR amplicons than capillary electrophoresis used by Moges et al (), we may have detected fewer alleles in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Using 50 SSR markers, including the 10 SSR markers we tested, Moges et al () found a higher level of genetic diversity between 163 Ethiopian Citrus C. gloeosporioides isolates. Because polyacrylamide gels are less sensitive to detect small size variations of SSR amplicons than capillary electrophoresis used by Moges et al (), we may have detected fewer alleles in the present study. However, our genetic diversity was higher than previously reported in Tunisia (Rhaiem & Taylor, ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations